MRI analysis of uterine ischaemia as a form of non-target embolisation following uterine artery embolisation: incidence, extent and outcome. Issue 12 (December 2021) - Naguib, N.N.N.; Kaltenbach, B.; Abdel-Karim, A.A.; Elabd, A.; Abd-Elsalam, H.; Hammerstingl, R.; Ackermann, H.; Vogl, T.J.; Nour-Eldin, N.-E.A.
Abstract : AIM: To study the incidence, extent and fate of uterine ischaemia as one of the forms of non-target embolisation following uterine artery embolisation (UAE), as detected on immediate post-embolisation and contrast-enhanced magnetic resonance imaging (MRI) examinations at the 3-month follow-up. MATERIALS AND METHODS: A retrospective study was undertaken comprising 43 women (mean age: 44.8 ± 3.79 years). MRI was performed before, immediately after (within 6 h), and 3 months after successful UAE. Areas of uterine ischaemia were identified on immediate post-embolisation MRI as regions of newly developed (compared to pre-embolisation MRI) absent enhancement within the uterus not corresponding to the location of the leiomyoma. The volume of the ischaemic region was calculated using the formula (height × length × width × 0.523). RESULTS: Uterine ischaemia was encountered in 29 patients (67.44%). The mean volume of the ischaemic region immediately after UAE was 29.29 ± 19.15 ml (range: 7.36–87.71 ml). At 3-month follow-up, it was 0.35 ± 0.95 ml (range: 0–3.5 ml) with 25 (86%) patients showing complete resolution of the ischaemia. The mean reduction in the volume of the ischaemic region at the 3-month follow-up was 98.24 ± 5.72% (range: 72–100%). This volume reduction was statistically significant ( p< 0.0001). CONCLUSION: Uterine ischaemia as a form of non-target embolisation following UAE might be encountered in up to two thirds of patients. These ischaemic areas are significantly reduced at the 3-month follow-up with up to 86% of cases showing complete reversibility of the ischaemia. Highlights: Uterine ischaemia following non-target embolisation may affect most of the patients. The uterine ischaemia regresses significantly within 3 months post embolisation. The uterine ischaemia post embolisation is completely reversible.